Advanced techniques applied to analyse the influence of the heat treatment on the mechanical properties, microstructure and texture of additively produced components from maraging steel. Issue 1 (August 2021) - Koukolíková, M; Brunát, V; Wolf, G; Simson, T; Koch, J
Abstract: The experimental program Metallic materials in the process chain of additive manufacturing is focused on the characterization of laser powder bed fused materials (L-PBF). Metallographic analysis, electron backscatter diffraction supported by micro tensile testing were used to analyse the material properties of the maraging steel MS1. The main goal of the research was to use advanced techniques to investigate the influence of the additive manufacturing with very fine powders, and subsequent heat treatment on the microstructure, texture and mechanical properties of the components from maraging steel.